2011
DOI: 10.4028/www.scientific.net/amr.347-353.1584
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity and Chemical Composition of Leaf Essential Oil from <i>Solidago canadensis L.</i> in China

Abstract: The essential oil was obtained at yield of 0.30% by hydrodistillation from fresh leaf tissue of Solidago canadensis L. collected from Zhejiang Province, China. GC and GC/MS analysis identified 46 components, representing 94.6% of the leaf oil. The main components were (-)germacrene D (28.4%), bornyl acetate (9.2%), D-Limonene (5.0%). The essential oil was tested for cytotoxic activities against three tumor cell lines. The inhibitory concentrations of the essential oil at 50% effect level (IC50) were 68.1 μg/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
(47 reference statements)
1
10
0
1
Order By: Relevance
“…The study of Li et al. (2012) [30] has demonstrated a cytotoxicity of the fresh leaves of S. canadensis E.O. on three tumor cell lines (human cervical carcinoma cell lines HeLa, human liver carcinoma cell lines PLC, and human hepatocellular carcinoma cell lines SMMC‐7721) with IC 50 of 156.9, 71.4 and 68.1 μg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Li et al. (2012) [30] has demonstrated a cytotoxicity of the fresh leaves of S. canadensis E.O. on three tumor cell lines (human cervical carcinoma cell lines HeLa, human liver carcinoma cell lines PLC, and human hepatocellular carcinoma cell lines SMMC‐7721) with IC 50 of 156.9, 71.4 and 68.1 μg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[29] These results were slightly similar to those we found in our study. The results of Kalemba and Thiem (2004) [27] on the analysis of the E.O from Poland have demonstrated that the major compounds were α-pinene (59.5 %), limonene ( [30] has demonstrated a cytotoxicity of the fresh leaves of S. canadensis E.O. on three tumor cell lines (human cervical carcinoma cell lines HeLa, human liver carcinoma cell lines PLC, and human hepatocellular carcinoma cell lines SMMC-7721) with IC 50 of 156.9, 71.4 and 68.1 μg/ml, respectively.…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…D-limonene and carvacrol, of the terpene family, showed to induce apoptosis through the mitochondrial pathway [58,59], similar to the results observed in our study. Another compound, Germacrene D, was found to exhibit a cytotoxic effect on HL-60 cells [60] and human cervical, liver, and hepatocellular carcinoma [61]. Alpha-tocopherol derivatives, another major constituent, has been found to induce cell death and inhibit viability, migration, and invasion of breast cancer cells [62].…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of the Solidago genus have been chemically and biologically previously reported to many species as S. altissima, S. gigantea (Fujita et al 1979), S. virgaurea (Fujita 1991), S. canadensis (Weyerstahl et al 1993;Kasali et al 2002), S. graminifolia (Kalemba 1992), S. virgaurea (Kalemba 1998), S. chilensis (Gressler et al 2003;Duarte et al 2005) and these biological activities described were antifungal and (Gressler et al 2003;Li et al 2011), antimicrobial (Duarte et al 2005). The essential oil from Solidago canadensis leaf was tested for cytotoxic activities against three tumor cell lines (Yoshihara et al 1969;Steliopoulos et al 2002).…”
Section: Introductionmentioning
confidence: 97%